2021
DOI: 10.1101/2021.09.01.458529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluid-structure interaction simulation of tissue degradation and its effects on intra-aneurysm hemodynamics

Abstract: Tissue degradation plays a crucial role in vascular diseases such as atherosclerosis and aneurysms. We present a novel finite element method-based approach to model the microscopic degradation of an aneurysmal wall due to its interaction with blood flow. The model is applied to study the combined effects of pulsatile flow and tissue degradation on the deformation and intra-aneurysm hemodynamics. Our computational analysis reveals that tissue degradation leads to a weakening of the aneurysmal wall, which manife… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…As mentioned above, in this work, we use a recently developed FSI framework to account for the interaction between blood flow and aneurysmal walls, and at the same time to capture the degradation of vascular tissues (Wang et al, 2021b). In this computational framework, a tissue degradation model (Balzani et al, 2012;Anttila et al, 2019) is combined with the opensource software, SimVascular/svFSI (2021) which is finiteelement-method-based and uses an arbitrary Lagrangian-Eulerian formulation of Navier-Stokes equations to model incompressible Newtonian fluid (blood) flows on moving domains (Vedula et al, 2017).…”
Section: Numerical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned above, in this work, we use a recently developed FSI framework to account for the interaction between blood flow and aneurysmal walls, and at the same time to capture the degradation of vascular tissues (Wang et al, 2021b). In this computational framework, a tissue degradation model (Balzani et al, 2012;Anttila et al, 2019) is combined with the opensource software, SimVascular/svFSI (2021) which is finiteelement-method-based and uses an arbitrary Lagrangian-Eulerian formulation of Navier-Stokes equations to model incompressible Newtonian fluid (blood) flows on moving domains (Vedula et al, 2017).…”
Section: Numerical Modelmentioning
confidence: 99%
“…The degradation model employed here has been validated in previous studies (Balzani et al, 2012;Anttila et al, 2019) and proved to reproduce the experimental cyclic responses of different types of arteries. The current model is able to account for stress softening (Balzani et al, 2012;Anttila et al, 2019;Wang et al, 2021b), a phenomenon commonly observed in biological tissues. The present study is qualitative research and a first step toward a more realistic model.…”
Section: Numerical Modelmentioning
confidence: 99%
See 3 more Smart Citations